Influence of Blood Platelets on Fibrinolysis - Holemans, Rudolf; Gross, Rudolf (Thrombosis and Haemostasis, 1961)
1. Human blood platelets contain a considerable amount of proactivator activity but no plasminogen activator activity or plasminogen. In test systems, containing streptokinase, the lysis of bovine fibrin is enhanced, depending upon the amount of platelets present.2. The platelet proactivator is completely destroyed by heating during 15 min at 70° C. Washing of platelets reduces their proactivator activity; however proactivator activity can still be found after ten washings.3. Bovine platelets do not contain proactivator activity. The similarity in the content in proactivator activity in plasma and platelets of both species, as well as the decrease of proactivator activity by washing, strongly suggests that the proactivator activity of human platelets is adsorbed on the platelet surface from the plasma.4. Both in human platelets and in bovine platelets, antifibrinolysin can be found. This factor is thermostable and is only slightly diminished by washing. The platelet antifibrinolysin seems for its larger part to be located in the platelets; only a small fraction may be adsorbed on their surface.5. The platelet antifibrinolytic activity can, depending upon the platelet concentration, be easily determined in systems containing urokinase or plasmin. Also in streptokinase-activated systems, bovine blood platelets have an inhibiting effect; human blood platelets inhibit streptokinase-induced fibrinolysis when their proactivator activity has been destroyed by heating. When streptokinase and unheated human blood platelets are tested on bovine fibrin the inhibitor effect is completely masked by the presence of proactivator.6. The clinical significance of these findings with regard to fibrinolysis occurring spontaneously or induced by streptokinase infusion, as well as their importance for the differentiation of proactivator and human plasminogen are discussed.